Assessment of malocclusion status, dentition status, and treatment needs among 15-year-old school children of Mangalore - Roshan Shetty; Vijaya Hegde; Pooja J Shetty (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: Dental caries and malocclusion are common dental public health problems. Surveys provide us with an insight into the oral health status and treatment needs and also help in proper treatment planning. Hence, the objective of this study was to assess the malocclusion status, dentition status, and treatment needs of 15-year-old school children of Mangalore. Methodology: A cross-sectional study of 1001 school children aged 15-year-old was conducted in Mangalore. Their malocclusion status, dentition status, and treatment needs were recorded using the WHO oral health assessment pro forma. Statistical analysis was done using Statistical Package for Social Sciences version 17. Descriptive statistics was obtained and Chi-square test was used. The level of significance was set at 0.05. Results: Decayed teeth were prevalent in 45.5% of the study subjects. Malocclusion was present in 30% of the study subjects. Teeth missing due to caries and those requiring extraction and prosthetic rehabilitation were significantly higher in government schools (P < 0.05). Malocclusion and treatment need was significantly higher in government schools (P < 0.05). Conclusion: From the present study, we can conclude that the school children aged 15 years of Mangalore had varied malocclusion status, dentition status, and treatment needs with significantly higher treatment needs and malocclusion among children of government school.